2016
DOI: 10.1007/s40268-016-0140-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lemon and Seville Orange Juices on the Pharmacokinetic Properties of Sildenafil in Healthy Subjects

Abstract: PurposeSeveral severe drug interactions have been reported when sildenafil, a potent drug for the treatment of erectile dysfunction, is co-administered with drugs or herbal remedies that inhibit cytochrome P450 (CYP) 3A4. This study evaluates the effects of two citrus fruit juices, lemon and Seville orange, on the pharmacokinetics of sildenafil in male healthy subjects following a single oral dose.MethodsWe conducted an open-label, three-way crossover study in nine healthy male volunteers. Participants receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
(25 reference statements)
0
13
0
1
Order By: Relevance
“…However, Abdelkawy et al. reported that lemon does not affect the pharmacokinetics of sildenafil . Based on this information, it was likely that the citrus fruits investigated in this study that contained more DHB than pummelo would induce drug interactions mediated by the inhibition of CYP3A4 and that citrus fruits that contained less DHB than lemon would be safe.…”
Section: Discussionmentioning
confidence: 73%
“…However, Abdelkawy et al. reported that lemon does not affect the pharmacokinetics of sildenafil . Based on this information, it was likely that the citrus fruits investigated in this study that contained more DHB than pummelo would induce drug interactions mediated by the inhibition of CYP3A4 and that citrus fruits that contained less DHB than lemon would be safe.…”
Section: Discussionmentioning
confidence: 73%
“…The primary active ingredients in Citrus responsible for these effects are the furanocoumarins bergapten, bergamottin, and 6′,7′‐dihydroxybergamottin (Guo et al ., ; Paine et al ., ; Fujita et al ., ; Messer et al ., ; Greenblatt et al ., ). Studies have shown that Seville, mandarin, and clementine orange juices have the potential to produce drug interactions (see, for example, Abdelkawy et al ., ; Theile et al ., ), presumably due to their furanocoumarin content. Gurley et al .…”
Section: Discussionmentioning
confidence: 99%
“…The primary active ingredients in Citrus responsible for these effects are the furanocoumarins bergapten, bergamottin, and 6 0 ,7 0 -dihydroxybergamottin (Guo et al, 2000;Paine et al, 2006;Fujita et al, 2008;Messer et al, 2011;Greenblatt et al, 2012). Studies have shown that Seville, mandarin, and clementine orange juices have the potential to produce drug interactions (see, for example, Abdelkawy et al, 2016;Theile et al, 2016), presumably due to their furanocoumarin content. Gurley et al (2004) showed that, in humans receiving 30.6 mg of p-synephrine per day in the form of a bitter orange (C. aurantium), no significant effects were observed on CYP3A4, CYP1A2, CYP2D6, or CYP2E1, the major drug-metabolizing cytochrome enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Tangeretin is present in the bitter orange peel of Seville orange, the Seville juice was reported to inhibit intestinal cytochrome P450 (CYP) isozyme 3A4, and P-glycoprotein was shown to affect colchicine metabolism and transport, which can lead to severe toxicity [ 76 ]. Sildenafil bioavailability is reported to be improved by Seville orange; this can be contributed to the inhibition of its intestinal first-pass effect of CYP3A4 and/or P-gp [ 77 ]. On the other hand, tangeretin was reported as a potent regioselective stimulator causing CYP3A4 induction [ 73 , 78 ].…”
Section: Tangeretin-drug Interactionsmentioning
confidence: 99%